Strain-tunable Zeeman splitting and optical properties of CrBr3/GeC van der Waals heterostructure - Z. Yang; J.L. Wang; G.C. Hu; X.B. Yuan; J.F. Ren; X.W. Zhao (Results in Physics, 2022)
We investigated the physical properties of CrBr3/GeC van der Waals heterostructures (vdWHs) by using the density functional theory (DFT) calculations. Due to the magnetic proximity effect, Zeeman splitting occurs in the energy band of the GeC. Tensile strain will induce the increasing of the Zeeman splitting, however, compressive strain will induce the decreasing of the Zeeman splitting. The band gap of the CrBr3/GeC vdWHs will undergo a direct to indirect transition when the strain changes. For the optical properties of the system, it is found that CrBr3/GeC vdWH has better light absorption performance in the infrared and visible light region comparing with that of the GeC monolayer. The light absorption capacity can also be adjusted by applying strain. The absorption peak in the infrared region gradually increases when the compressive strain changes from −1% to −5%. The physical properties exhibited from CrBr3/GeC vdWH indicate its application potential in the field of optoelectronic devices.